Optical recording in Se(Te)/As2S3 multilayers - Kokenyesi, S.; Ivan, I.; Malyovanik, M.; Messaddeq, S. H. [UNESP]; Messaddeq, Y. [UNESP]; Ribeiro, S. J.L. [UNESP] (My University, 2006)
The development of Te containing nanoscaled, compositionally modulated Te/As2S3 multilayer structures enables the realisation of optical recording in real time with a CW He-Ne laser illumination (λ=633 nm) with improved recording parameters in comparison with known Se/As 2S3 structures. It is established that the efficiency of the recording process depends on the light stimulated interdiffusion and thickness of sub-layers.